Approximate Boundary Controllability for Semilinear Delay Differential Equations - Lianwen Wang (Journal of Applied Mathematics)
This paper considers the approximate controllability for a class of semilinear delay control systems described by a semigroup formulation with boundary control. Sufficient conditions for approximate controllability are established provided the approximate controllability of corresponding linear systems.